(untitled) (Indian Journal of Public Health Research & Development, 2020)
Context: Objective: Foot ulcer is one of the diabetic complications that causes death in the world. Preventive behavior can be used to prevent diabetic foot ulcers. Therefore, this study aims at developing a model of diabetic foot ulcer prevention based on psychosocial, attitude, intention and coping mechanisms. The study used a cross-sectional study design to look at the relationship between variables using simple random sampling in 329 respondents, ages 18-85 years, who made an inspection visit at a health care center. The research instrument consisted of psychosocial variables namely knowledge and stress, attitude, intention, coping mechanisms, and foot ulcer prevention . Furthermore, the data were analyzed using SEM-PLS software. Results shows most of the respondents were in the youth category ages 18 - 65 years. Analysis of shows that there is a psychosocial influence on attitude T = 10,92, there is an effect of attitude on intention T = 2,43, there is an influence of intention on coping mechanisms T = 8,28, there is an influence of intention on Foot ulcer prevention T = 2,57, there is an influence of coping mechanisms on foot injury prevention T = 5,02. Knowledge, stress, attitude, intention and coping mechanisms contribute to prevent diabetes foot injuries. The Conclusions Knowledge, stress and attitude variables contributed the most indirectly to diabetes foot injury prevention. Contributions are directly affected by coping mechanisms and intentions.